Improving the learning outcome for students in Human Physiology by a problem-based learning approach - Kjøbsted, Rasmus (Improving University Science Teaching and Learning, 2023)
A problem-based learning (PBL) approach can be defined as teacherconstructed problems presented to a small group of students whose mission it is to discuss, describe and produce tentative explanations for the given problem or case study (Norman & Schmidt, 1992). Although PBL does not seem to improve general problem-solving skills, evidence suggests that PBL enhances retention of knowledge, intrinsic interest in the subject matter as well as self-directed learning skills (Norman & Schmidt, 1992). In this project report I will therefore investigate how PBL is adapted and perceived in classroom teaching of university students studying human physiology for the purpose of accommodating learning and specific intended learning outcomes (ILOs).